A percepção ambiental dos agricultores vinculados a uma Rede de Referência em agricultura familiar: uma análise sobre as práticas agroecológicas e a qualidade de vida. - Altemburg, Shirley Grazieli Nascimento (2011)
This work was performed on 11 family farms located in seven counties included in the project "Participatory research in reference network for ecologically based family agriculture in the southern region of Rio Grande do Sul", coordinated by Embrapa Clima Temperado (Embrapa Temperate Climate) Pelotas, RS, Brazil. The overall objective of the study was to verify the aspects related to the environmental perception of farmers and verify the relation between the use of agro-ecological practices and quality of life in rural. The methodology used to conduct the study was analysis of interviews and observation. They were carried out through visits to the properties. Based on the obtained results, it was possible to conclude that agroecology provides an environmental and social emancipation of the farmers. In this sense, the studied properties have a high degree of environmental preservation, that is directly related to the management techniques used by the production system of ecological basis. Regarding the quality of life in rural, some points were identified as necessary for a greater appreciation of family farming with ecological base in the southern territory. Thus, initiatives such as dissemination of production with ecological base and educational activities adequated to the field in order to help young people stay on the field, are the major concerns of the farmers. In general, this study sought to help formulate strategies that contribute to the dissemination of the ecological based production in the southern territory, since it, besides ensuring environmental preservation, reflects in the quality of life of farmers.